2016
DOI: 10.4097/kjae.2016.69.5.514
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest after sugammadex administration in a patient with variant angina: a case report

Abstract: A 76-year-old man with no notable medical history was scheduled for a robot-assisted radical prostatectomy. After the operation, he was given sugammadex. Two minutes later, ventricular premature contraction bigeminy began, followed by cardiac arrest. Cardiac arrest occurred three times and cardiopulmonary resuscitation was done. The patient recovered after the third cardiopulmonary resuscitation and was transferred to the intensive care unit. Coronary angiography was done on postoperative day 1. The patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…Thus, echocardiography finding does not exclude a diagnosis of Kounis syndrome. A previous case report describing profound bradycardia with severe hypotension after sugammadex administration also mentions the simultaneous appearance of ST change on ECG [9]. This report confirmed coronary vasospasm provoked by ergonovine on coronary angiography postoperatively.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, echocardiography finding does not exclude a diagnosis of Kounis syndrome. A previous case report describing profound bradycardia with severe hypotension after sugammadex administration also mentions the simultaneous appearance of ST change on ECG [9]. This report confirmed coronary vasospasm provoked by ergonovine on coronary angiography postoperatively.…”
Section: Discussionsupporting
confidence: 78%
“…In this case, approximately 4 min after sugammadex administration, the patient's heart rate decreased to 36 bpm accompanied by severe hypotension, which was unresponsive to intravenous atropine but recovered with intravenous adrenaline. Some case reports have described severe bradycardia associated with sugammadex [4][5][6][7][8][9]. Sugammadex-induced bradycardia is not due to cholinergic effects as it has been noted even in a patient with a denervated, transplanted heart [8]; however, no other mechanism has been postulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 There are only a few case presentations that show coronary vasospasm may be correlated with sugammadex. 16,17 The study, in which the hemodynamic effects of sugammadex and neostigmine on cardiac patients are compared, has found that sugammadex is more stable regarding cardiac function but causes a significant decrease in heart rate within the first minute after its administration. 3 So the effects of sugammadex on cardiovascular system are not very well-known.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is considered to be a safe and well-tolerated drug, concerns about the risk of drug-induced hypersensitivity reactions to sugammadex have emerged from case reports [3][4][5]. Among case reports about cardiac arrests that occurred after the administration of sugammadex, no cases of cardiac arrest related to Kounis syndrome induced by sugammadex have been reported [6,7].…”
Section: Introductionmentioning
confidence: 99%